Development of a Selective Medium for Isolation of Helicobacter pylori from Cattle and Beef Samples - Stevenson, Timothy H. (American Society for Microbiology, 2000)
Helicobacter pylori has been isolated from the human stomach with media containing only minimal selective agents. However, current research on the transmission and sources of infection requires more selective media due to the higher numbers of contaminants in environmental, oral, and fecal samples. The objective of this study was to develop and evaluate detection techniques that are sufficiently selective to isolate H. pylori from potential animal and food sources. Since H. pylori survives in the acidic environment of the stomach, low pH with added urea was studied as a potential selective combination. H. pylori grew fairly well on H. pylori Special Peptone plating medium supplemented with 10 mM urea at pH 4.5, but this pH did not sufficiently inhibit the growth of contaminants. Various antibiotic combinations were then compared, and a combination consisting of 10 mg of vancomycin per liter, 5 mg of amphotericin B per liter, 10 mg of cefsulodin per liter, 62,000 IU of polymyxin B sulfate per liter, 40 mg of trimethoprim per liter, and 20 mg of sulfamethoxazole per liter proved to be highly selective but still allowed robust colonies of H. pylori to grow. This medium was highly selective for recovering H. pylori from cattle and beef samples, and it is possible that it could be used to enhance the recovery of this bacterium from human and environmental samples, which may be contaminated with large numbers of competing microorganisms.